Drying Kinetics of Cassava Chips (Manihot esculenta crantz) in Microwave - García-Mogollón, Carlos; Torregroza-Espinosa, Angélica; Torregroza-Espinosa, Angélica; Sierra-Bautista, Mauricio; Sierra-Bautista, Mauricio (Rev. Téc. Fac. Ing. Univ. Zulia, 2016)
Drying cassava chips (Manihot esculenta crantz) to 0.4cm thick was made in a microwave oven; the effect of power, diameter and weight of the chips was evaluated using an experimental design completely randomized factorial arrangement 33 corresponding to the categorical variable with three power levels (140, 280 and 560W), diameter of the chip (2, 3 and 4 cm), weight cassava chips (20, 35 and 50 g), with three replicates for a total of 81 experimental units. Tukey”™s test was applied with a significance level of p 99%). The shortest drying time was obtained when it was performed at 560W in 4cm diameter chips (13,3min) and longer 140W was obtained (89,3min) chips of 2 cm.